(untitled) (Archive of Conferences, 2022)
The attentiveness of the scholars on linguistic pragmatics is determined by moving forward the ideas of the priority of content and secondary position of expression. The existence of pragmatic meaning is admitted by many linguists. The term “pragmatic meaning” or the second name “pragmatic aspect” is widely used in current language sphere. Its place and part in the content of the meaning structure of the word, content filling of the pragmatic meaning or aspect is being explained